PERSEPSI DAN MINAT PEMUDA TERHADAP PEKERJAAN SEBAGAI PETANI DI DESA WUWUK KECAMATAN TARERAN KABUPATEN MINAHASA SELATAN - Mikael Fernando Tampi; Rine ., Kaunang; Tommy F. Lolowang (Sam Ratulangi University, 2021)
This study aims to describe the perceptions and interests of youth towards occupation as farmers in Wuwuk Village, Tareran District, South Minahasa Regency. The sampling method in this study used a purposive sampling technique. The data used are primary data obtained through direct surveys in the field through interviews using prepared questionnaires and documentation and secondary data obtained from literature studies and agencies related to the data needed in this study. The analytical method used is descriptive analysis by describing the data that has been collected. The results of this study indicate that the youth of Wuwuk Village have a good perception towards occupation as farmers, although the youths are aware that agricultural businesses have a risk of business failure. A fairly good perception of youth towards occupation as farmers, makes the youth of Wuwuk Village still interested in working as farmers. The youth of Wuwuk Village still consider that work as a farmer provides sufficient income and provides benefits because the farmer family is able to meet the needs of their families and can even send their children to college.